Nanoemulsões de carvacrol ou óleo essencial de orégano para o controle in vitro de Fusarium oxysporum f. sp. lycopersici - Fontes, Caroline de Souza (2019)
The Fusarium wilt control by the use of resistant cultivar is not completely efficient. Although essential oils (EO’s) are a potential alternative for the control of this disease, their use in in vivo conditions is limited because of the low solubility in water and photodegradation, making necessary the use of appropriate technology. Therefore, the objective of this work was to produce stable nanoemulsions using carvacrol and EO of oregano (Origanum vulgare L.), in order to evaluate its effect on F. oxysporum f. sp. lycopersici. Carvacrol and EO from oregano were analyzed by GC-MS and CG-DIC. For OE of oregano were found as major constituents carvacrol (49.97%), p-cymene (12.02%), y-terpinene (8.77%) and thymol (7.73%). Nanoemulsions were prepared using Tween 80®, octanol and ultrasonic homogenizer. The effect of the independent variables (ultrasonic homogenization time, surfactant content and cosurfactant content) in the preparation of nanoemulsions was evaluated using the central rotational compound design (CRCD) using factorial scheme 23. It was possible to obtain stable nanoemulsions of carvacrol with diameters between 21.38 to 12.80 nm and EO of oregano with diameters of 28.60 to 12.81 nm. The independent variables, as well as their interactions, did not show a significant effect in relation to the average droplet diameter and the zeta potential, both for the analyzes performed with carvacrol and for EO of oregano. The nanoemulsions of carvacrol and EO of oregano showed an inhibitory effect on the fungus, being the oregano EO nanoemulsion more efficient. It is expected that in the future stage, nanoemulsions can be tested in vivo in control against Fusarium wilt.